Mastering object-oriented Python : grasp the intricacies of object-oriented programming in Python in order to efficiency build powerful real-world applications /: grasp the intricacies of object-oriented programming in Python in order to efficiency build powerful real-world applications. (2014) - Lott, Steven F
No abstract available